Огляд поточного стану та перспектив розвитку сонячної енергетики в україні - Sverdlova , Anastasiia (General Energy Institute of the National Academy of Sciences of Ukraine, 2022)
This paper analyzes the prospects for developing solar power generation systems and the economic feasibility of further industry development. The state of global solar energy, its expansion potential, and Ukraine's position in the total statistics are examined. The rate of increase in the introduction of alternative types of energy has been determined. Statistical data on the number of commissioned power plants and the electricity they produced were analyzed. Solar energy is one of the most promising and powerful renewable energy sources. As a result of the analysis, it was concluded that Ukraine is gradually taking essential steps to expand the use of solar energy, developing a regulatory and legislative basis for the service, implementation, optimization, and stimulation of households to implement and build solar power plants. The relevance and expediency of the use of solar energy in connection with the constant growth of the cost of electricity and the future forecast of the increase of public investments in the industry at the global level are characterized. According to the analysis of statistical data and forthcoming plans for solar energy development, high rates of its growth in Ukraine have been determined. The consequences the war has on the solar energy industry are described. It is explained that, due to the war, half of the renewable energy objects are under threat of complete or partial destruction, in particular, 47% of solar power plants are located in regions where active fighting continues. The general trend of post-war development will be an increase in the share of solar energy in the overall energy balance. This will be facilitated by eliminating financial and legislative restrictions on the development of renewable energy, expanding opportunities for the export of electricity from renewable energy sources, and considering the green course, which is focused on clean energy.